The use of cuadernia educational software in the teaching - learning process and in the academic performance of mathematics of the students of the 5th grade of secondary school of the educational institution No. 5143 Escuela de Talentos. Callao. - Encalada Diaz, Ivan Angel (2021)
The purpose of this research was to determine how the Cuadernia educational software contributes to the teaching - learning process and the academic performance of Mathematics in fifth year students of the educational institution Nr. 5143 Talent School of the Constitutional Province of Callao. The research was of quantitative approach, of applied type and quasi-experimental design. We worked with two homogeneous groups, one experimental and the other control students of the fifth year of secondary education, female and male, between 15 and 17 years. The control group consisted of 25 students and the experimental group of 25 students. Most students have access to a computer and Internet service either at home or in a public booth near their home, they manage social networks, minimum handling of Word, Excel, Power Point, and information search engines. To collect the results of teaching-learning process of mathematics was used a written test and to collect the results of academic achievement of mathematics we used the official record with grades obtained by students in a given period. In order to verify the results, the test of difference of means (test t) was used, which allowed to make the comparison between the pre-test and post-test of each group and between groups. It was concluded that if there was a statistically significant difference at a confidence level of 0.05 between the pre-test and post-test of the experimental group after applying the Cuadernia educational software.